Litter decomposition of Rhizophora stylosa in Sabang-Weh Island, Aceh, Indonesia; evidence from mass loss and nutrients - IRMA DEWIYANTI (Society for Indonesian Biodiversity, 2010)
Dewiyanti I (2010) Litter decomposition of Rhizophora stylosa in Sabang-Weh Island, Aceh, Indonesia; evidence from mass loss and nutrients. Biodiversitas 11: 139-144. Mangrove is an essential coastal ecosystem that provides nutrients to estuarine and its surrounding environments through its litter decomposition. This vegetation can be considered as an important ecosystem in food web along the coast. The research was conducted in mangrove forest in Sabang-Weh Island, Aceh. Rhizophora stylosa was dominant species of mangrove in the study area that still remains after tsunami catastrophe in 2004. This study was conducted from February to April 2008, and the purposes were to obtain the decomposition rate of senescent leaves and to measure mass loss, and nutrient contents of decomposing leaves under different inundation regime. Three plots were established in each site. Decomposition of R. stylosa leaves were studied by using litter bag technique. They were made of synthetic nylon which had size 20x30 cm and mesh size was 1x1.25 mm2. Senescent leaves were used because they present major leaves on the forest floor and started to decay. Remaining leaves decreased during experiment period because decomposition process had been taking place in the study area. Time required for decomposing a half of theinitial material (t50) was 67 days and 63 days for site next to the land and site next to the sea, respectively. The decay rate can be expressed by the decay coefficient (K) and the results of K were 0.010 and 0.011 (d-1). The value of carbon (C), nitrogen (N), C: N ratio and phosphorous (P) during decomposition periods were no significant difference in sites but significant difference in time. The C: N ratio of decomposing leaves decreased in both sites. Low C: N ratio in the last of observation indicated that R. stylosa leaves weredecomposed easier at the end of observation than that in the beginning of observation.Key words: Rhizophora stylosa, leaves litter, mass loss, nutrients, Aceh.